DESPRE PUTEREA EXEMPLULUI - HARJEVSCHI, director general al BM „B.P. Hasdeu”, președinte al ABRM, Mariana (BIBLIOPOLIS, 2020)
The author informes about her documentary visit to the National Library of Romania and the “M. Sadoveanu” Metropolitan Library from Bucharest, support by Novateca Program. Mrs Mariana Harjevschi, as a general manager of “B.P. Hasdeu“, Municipal Library shares about library services, strategies and projects.